Bromodomain inhibition of the coactivators CBP/EP300 facilitate cellular reprogramming - Ebrahimi, Ayyub (Nat Chem Biol, 2019)
Silencing of the somatic cell-type specific genes is a critical yet poorly understood step in reprogramming. To uncover pathways that maintain cell identity, we performed a reprogramming screen using inhibitors of chromatin factors. Here we identify acetyl-lysine competitive inhibitors targeting the bromodomains of coactivators CBP and EP300 as potent enhancers of reprogramming. These inhibitors accelerate reprogramming, are critical during its early stages and, when combined with DOT1L inhibition, enable efficient derivation of human iPSCs with OCT4 and SOX2. In contrast, catalytic inhibition of CBP/EP300 prevents iPSC formation, suggesting distinct functions for different co-activator domains in reprogramming. CBP/EP300 bromodomain inhibition decreases somatic-specific gene expression, histone H3 lysine 27 acetylation (H3K27Ac) and chromatin accessibility at target promoters and enhancers. The master mesenchymal transcription factor PRRX1 is one such functionally important target of CBP/EP300 bromodomain inhibition. Collectively, these results show that CBP/EP300 bromodomains sustain cell type specific gene expression and maintain cell identity.